ANALISIS TAHAP KESUKARAN BAGI TOPIK DALAM KURSUS TEKNOLOGI ELEKTRIK 2 DARI PERSPEKTIF PELAJAR - Sharif, Mohd Zamri; Foong, Lee Ming (Online Journal for TVET Practitioners, 2018)
Electrical Technology 2 (TE2) is one of the compulsory course for the students from Bachelor of Vocational Education (Electrical and Electronic Engineering) at Faculty of Technical and Vocational Education. This course consists of four main topics and sub-topic. Studentsâ€™ achievement analysis in this course for the previous six semester showed that majority of them score gred B+ and below. Thus, this study was conducted to identify the difficulty level for each sub-topic consisted in TE2 course. The research design for this study was using quantitative approach through survey method. Questionnaire was employed as instrument in this study. Samples of this study involved of 20 students that learn this this course using purposive random sampling technique. Collected data was analyzed using frequency and percentage. Result shown that the sub-topic of â€œVoltage and phase balance in star and delta connectionâ€ from the third topic was the most difficult to understand and mastery by students. This results agreed by two lectures who taught this course before through interview. This findings can assist lectures to enforce this sub-topic during conducted learning and teaching process for TE 2 course.